2022
DOI: 10.3389/fvets.2022.826367
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Parameters and Estimating Extra-Label Tissue Withdrawal Intervals Using Three Approaches and Various Matrices for Domestic Laying Chickens Following Meloxicam Administration

Abstract: Meloxicam is commonly prescribed for treating chickens in backyard or small commercial operations despite a paucity of scientific data establishing tissue withdrawal interval recommendations following extra-label drug use (ELDU). Historically, ELDU withdrawal intervals (WDIs) following meloxicam administration to chickens have been based on the time when meloxicam concentrations fall below detectable concentrations in plasma and egg samples. To date, no studies have addressed tissue residues. ELDU WDIs are com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In China, meloxicam has been approved in laying hens to alleviate pain; however, its use is prohibited during the laying period to prevent the possible drug residues in the eggs. There are some citations regarding the pharmacokinetics of meloxicam in laying hens (Richards et al, 2022; Souza et al, 2017, 2018, and 2021); however, the extravascular bioavailability is rarely reported. The empirical dose range of meloxicam in birds was 0.1–2.0 mg/kg (Cole et al, 2009; Marx, 2006; Pollock et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In China, meloxicam has been approved in laying hens to alleviate pain; however, its use is prohibited during the laying period to prevent the possible drug residues in the eggs. There are some citations regarding the pharmacokinetics of meloxicam in laying hens (Richards et al, 2022; Souza et al, 2017, 2018, and 2021); however, the extravascular bioavailability is rarely reported. The empirical dose range of meloxicam in birds was 0.1–2.0 mg/kg (Cole et al, 2009; Marx, 2006; Pollock et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The physiologically based pharmacokinetic ( PBPK ) modeling combined with Monte Carlo simulations was also applied to determine the WDIs of meloxicam in laying hens, which were 22 and 4 d in yolk and white after 14 repeated oral dosing (1 mg/kg) at 24-h intervals ( Yuan et al, 2022a ). In another backyard chickens study ( Richards et al, 2022 ), 3 different model-based approaches (nonlinear mixed-effect model, artificial neural network, and support vector machine) were used to determine WDIs of meloxicam in the tissues rather than eggs.…”
Section: Discussionmentioning
confidence: 99%